Analysis of institutional factors as part of the component of economic freedom as a background of improvement of structural proportions in the context of improving governance - Nikonenko, Uliana; Medynska, Tetyana; Bilotskyi, Oleksandr; Baran, Mariia; Shevchuk, Inna (Business, Management and Economics Engineering, 2020)
Purpose – the main purpose of the study is to analyze the institutional factors that are usually considered as components of economic freedom, as well as to assess the level of economic freedom as a prerequisite for improving structural proportions and stimulating the investment process in an economy with excess raw materials sector (such as Ukraine). Research methodology – the methodological basis is a system of complementary mathematical, general scientific and special methods, in particular system-structural comparison of retrospective, diagnostics and mathematical methods of studying possible dependence, general methods of analysis and synthesis, etc. Findings – the main result of the study is that increasing the degree of economic freedom in Ukraine contributes to structural shifts in favour of non-resource exports. Research limitations – our assessment methodology does not take into account the specifics of most European countries and is mainly aimed at countries of Eastern Europe so far. Practical implications – our proposed methodology for assessing the dependence of structural changes in a country’s exports on the economic freedom index IEF can be used in the practice of public administration in countries of such countries as Ukraine and others. Originality/Value – a proposed method for estimating the dependence of structural changes in Ukrainian exports on the IEF Index of Economic Freedom.